A Study of the Role of Initiators in Creating Sustainability of Kampung Gagot Tourism Village - Benedicta Evienia P; Andang Wirawan B; Penny Handayani (Proceedings Series on Social Sciences & Humanities, 2024)
Background: To achieve the Sustainable Development Goals (SDGs), every area with social problems needs to carry out activities that can encourage the community or environment to carry out empowerment. Empowerment is an essential strategy in increasing the role of the community or society in increasing their potential to be more independent and work. This research aims to analyze the role of external agents in the development of Kampung Gagot Tourism Village, one of the leading destinations in Banjarnegara Regency. The active participation of the local community influences the current success of Kampung Gagot Tourism Village. However, the research reveals the unexpected role of external agents who act as directors in developing this area. Method: The research method was qualitative, with explanations through descriptive techniques. Data were collected through observation and in-depth interviews with informants selected using purposive sampling. Results: The results highlighted the role of initiators as conceptors, information mouthpieces, and tourism ambassadors in developing tourism in Kampung Gagot Tourism Village. Conclusion: The obstacles encountered need to be addressed wisely, and the recommended approach is to involve the local community, especially the younger generation, to become an independent tourist destination, reducing dependence on the initiator.